The Impact of Intellectual Capital Efficiency on Company Performance and Firm’s Value - Liani, Mei; Kembaren, Sula Yosege Sembiring; Pendrian, Okder (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Business competition forces companies to strengthen their competitive advantage to survive and grow sustainably. Companies that survive in the competition will impact company performance and firm value. The factor that is thought to influence the company's competitive advantage is intellectual capital. This study aims to prove the effect of intellectual capital efficiency on financial performance and firm value. The method used is quantitative explanatory. The variable Intellectual Capital is measured by the VAIC (Value Added Intellectual Coefficient) method developed by Pulic (2000), company performance is measured by Return on Equity (ROE) and Earnings per Share (EPS), and the Firm’s Value is measured by Tobin's Q. Using purposive sampling on a population of 766 companies listed on the Indonesia Stock Exchange, this study took a sample of 409 companies using data from 2017 to 2021. The data were processed using Pearson Correlation Product Moment statistical tests and Single Linear Regression. The results show that Intellectual Capital efficiency significantly affects a company’s performance with a correlation level of 0.479 and an explanation rate of 37.3%; Intellectual Capital efficiency significantly affects firm value with a correlation level of 0.412 and an explanation rate of 41.83%. With segregated data, the result shows that the explanatory level in the technology and finance industry is greater than in other industries.